OH radicals reactivity towards phenol-related pollutants in water: temperature dependence of the rate constants and novel insights into the [OH–phenol]˙ adduct formation. Issue 3 (18th December 2019) - Kroflič, Ana; Schaefer, Thomas; Huš, Matej; Phuoc Le, Hoa; Otto, Tobias; Herrmann, Hartmut
Abstract : Relevance: a kinetic study on aqueous-phase reactions between OH˙ and phenolic compounds reveals structure-related differences in the transition state formation. Abstract : Substituted phenols are known to readily react with the hydroxyl radical (OH˙), which is the most powerful atmospheric oxidant and is also most often used in advanced oxidation processes (AOP) for wastewater treatment. We report temperature-dependent (278.15–318.15 K) second order kinetic rate constants for the aqueous-phase reactions of OH˙ with phenol and four substituted phenols: catechol, phloroglucinol, pyrogallol and 3-methylcatechol, with the last two measured for the first time. The constructed Hammett plots for mono- and di-substituted phenols have the potential to be further applied for predicting the reaction rate constants of other substituted phenols at 298.15 K. This will significantly facilitate the optimization of AOP and improve the predictive capabilities of atmospheric multiphase models in the future. Moreover, an advancement in the understanding of the underlying mechanism, i.e. OH˙ addition to the aromatic ring is made by theoretical calculations at the M06-2X level. We demonstrate that the position of substituents on the aromatic ring is important for the [OH–phenol]˙ adduct formation, which is supported by the experiment and theoretical calculations. Adjacent and nonadjacent electron donor/acceptor substituents differently impact the interplay between the activation energy and entropy. We also show that explicit solvation has to be accounted for in theoretical models in order to explicitly describe the formation of the transition state.